The good heart : His Holiness the Dalai Lama explores the heart of Christianity and of humanity - Gyatso. Tenzin (London : Rider, 2002)
In this accessible book, His Holiness the Dalai Lama considers such well-known Gospel passages as the Sermon on the Mount, the Healing of the Sick and the Resurrection.
Keywords: Bible -- Gospels -- Criticism, interpretation, etc; Bible -- Gospels; Buddhist literature -- Relations to the New Testament